FENOMEMOLOGI NGIRING PEMUJAAAN IDA RATU GEDE MAS MACALING DALEM PED NUSA PENIDA KABUPATEN KLUNGKUNG (Genta Hredaya: Media Informasi Ilmiah Filsafat Hindu, 2024)
This study aims to explore the phenomenology of worship of Ida Ratu Gede Mas Macaling at Pura Dalem Ped, Nusa Penida, Klungkung Regency. The phenomenon of "ngiring" or following the worship of Ida Ratu Gede Mas Macaling is a tradition that marks the religious and cultural aspects of the Balinese Hindu community. This study uses a phenomenological method with a qualitative descriptive approach to understand the religious experience and social meaning behind this worship. Data were collected through field observations, interviews with worshipers, and literature studies. The results of the study indicate that the practice of "ngiring" this worship is not only a form of religious devotion but also functions as a reinforcement of the cultural and spiritual identity of the Hindu community in Bali.
Keywords: phenomenology, ida ratu gede mas macaling, ngiring